Eksplorasi Segmentasi Pasar dan Motivasi Wisatawan Kuliner di Gudeg Pawon Yogyakarta - Hanggraito, Ahmadintya Anggit; Budiani, Budiani (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p18, 2021)
Studies on culinary tourists in Yogyakartais rarely explored in depth. In fact, Yogyakarta has become an area with various culinary attractions that have a variety of local foods. Gudeg Pawon is one of the top culinary destinations in Yogyakarta. Through a descriptive method with a qualitative approach, this research explores market segmentation and motivation of culinary tourists in Gudeg Pawon. The results of this study explain that the types of experiencers and enjoyers can represent the market segmentation of culinary tourism in Gudeg Pawon. In addition, there is a structured pattern in showing the main motivating factors for culinary tourists in Gudeg Pawon. Exploration of market segmentation and motivation of culinary tourists can be a deep consideration regarding the management of local food which has great potential in the development of new culinary tourism atractions. Keywords: Culinary Tourism, Market Segmentation, Tourist Motivation, Local Foods